Inspiratory muscle training improves 100 and 200 m swimming performance - Kilding, A. E.; Brown, S.; McConnel, A. K. (European Journal of Applied Physiology, 2010)
Inspiratory muscle training (IMT) has been shown to improve time trial performance in competitive athletes across a range of sports. Surprisingly, however, the effect of specific IMT on surface swimming performance remains un-investigated. Similarly, it is not known whether any ergogenic influence of IMT upon swimming performance is confined to specific race distances. To determine the influence of IMT upon swimming performance over 3 competitive distances, 16 competitive club-level swimmers were assigned at random to either an experimental (pressure threshold IMT) or sham IMT placebo control group. Participants performed a series of physiological and performance tests, before and following 6 weeks of IMT, including (1) an incremental swim test to the limit of tolerance to determine lactate, heart rate and perceived exertion responses; (2) standard measures of lung function (forced vital capacity, forced expiratory volume in 1 s, peak expiratory flow) and maximal inspiratory pressure (MIP); and (3) 100, 200 and 400 m swim time trials. Training utilised a hand-held pressure threshold device and consisted of 30 repetitions, twice per day. Relative to control, the IMT group showed the following percentage changes in swim times: 100 m, -1.70% (90% confidence limits, ±1.4%), 200 m, -1.5% (±1.0), and 400 m, 0.6% (±1.2). Large effects were observed for MIP and rates of perceived exertion. In conclusion, 6 weeks of IMT has a small positive effect on swimming performance in club-level trained swimmers in events shorter than 400 m.